THREE-PHASE TRANSFORMER PARAMETERS CALCULATION CONSIDERING THE CORE SATURATION FOR THE MATLAB-SIMULINK TRANSFORMER MODEL - I. V. Novash; Yu. V. Rumiantsev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
This article describes the parameters calculation for the three-phase two-winding power transformer model taken from the SimPowerSystems library, which is the part of the MatLab- Simulink environment. Presented methodology is based on the power transformer nameplate data usage. Particular attention is paid to the power transformer magnetization curve para- meters  calculation.  The  methodology  of  the  three-phase  two-winding  power  transformer model parameters calculation considering the magnetization curve nonlinearity isn’t presented in Russian-and English-language sources. Power transformers demo models described in the SimPowerSystems user’s guide have already calculated parameters, but without reference to the sources of their determination. A power transformer is a nonlinear element of the power system, that’s why for its performance analysis in different modes of operation is necessary to have the magnetization curve parameters.The process analysis during no-load energizing of the power transformer is of special interest. This regime is accompanied by the inrush current on the supply side of the power transformer, which is several times larger than the transformer rated current. Sharp rising of the magnetizing current is explained by the magnetic core saturation. Therefore, magnetiza- tion characteristic accounting during transformer no-load energizing modeling is a mandatory requirement. Article authors attempt to put all calculating formulas in a more convenient form and validate the power transformer nonlinear magnetization characteristics parameters calcu- lation. Inrush current oscillograms obtained during the simulation experiment confirmed the adequacy of the calculated model parameters.